The functions of territories of advanced socio-economic development to attract private capital in the context of the formation of a new model of economic growth - N. S. Stepanov (Вестник университета)
The purpose of this study is to analyze the concept of territories of advanced socio-economic development and their role in the development of regions through the synergy of instruments for attracting private capital and mitigating the consequences of economic crises. The research methods used were systematization in terms of analyzing the essence of special economic zones, generalization of concepts analyzing the functions of territories of advanced development in Russia, a graphical method of presenting information. To achieve the purpose of the study, the following tasks have been solved: the essence of special economic zones and their role in the economic development of the state has been clarified; an analysis of the functioning of the territories of the advanced in Russia has been presented: the number of residents and jobs, the amount of declared investments are growing annually. The results of the study include: systematization of characteristics and statistical data on the functioning of territories of advanced socio-economic development in Russia; justification of the insufficient effectiveness of such territories and the functions performed by them; clarification of the need to activate the main function of the territories of advanced socio-economic development to attract private capital.